Seduction and Healing in Architectural Design: Can Contemporary Consumption Spaces Heal? - Trivic, Zdravko (iUniverse, 2022)
Questions, Hypotheses & Conjectures: Discussions on Projects by Early Stage and Senior Design Researchers